2013
DOI: 10.1074/jbc.m112.395087
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Phosphatase Myotubularin-related Protein 6 (MTMR6) Is Regulated by Small GTPase Rab1B in the Early Secretory and Autophagic Pathways

Abstract: Background:The activity of myotubularin-related protein 6 (MTMR6) is regulated by an unknown mechanism. Results: The cellular localization of MTMR6 was regulated by Rab1B via the GRAM domain. They were functionally related in the early secretory and autophagic pathways. Conclusion: MTMR6 is regulated by Rab1B via the conserved GRAM domain. Significance: Our results reveal a novel regulatory mechanism of MTM phosphatases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 65 publications
3
35
1
Order By: Relevance
“…Although GEFs and GDIs are thought to be the predominant binding partners for GDPbound Rabs, other interacting proteins have been described. For instance, the GRAM domain of myotubularin-related protein 6 (MTMR6) interacts preferentially with GDP-bound Rab1b (44). Furthermore, protrudin interacts preferentially with GDP-bound Rab11 (45).…”
Section: Endogenous Rab13 Associates With Membranes Through Protein-pmentioning
confidence: 99%
“…Although GEFs and GDIs are thought to be the predominant binding partners for GDPbound Rabs, other interacting proteins have been described. For instance, the GRAM domain of myotubularin-related protein 6 (MTMR6) interacts preferentially with GDP-bound Rab1b (44). Furthermore, protrudin interacts preferentially with GDP-bound Rab11 (45).…”
Section: Endogenous Rab13 Associates With Membranes Through Protein-pmentioning
confidence: 99%
“…RAB proteins cycle between an active GTP-bound state and an inactive GDPbound state and act by recruiting effector proteins to mediate trafficking between different compartments (Stenmark, 2009). RAB1 regulates vesicular transport between the ER and Golgi, and was recently found to be important for omegasome formation (Mochizuki et al, 2013). The yeast TRAPPIII complex acts as an autophagy-specific guanine nucleotide exchange factor (GEF) for Ypt1 (the yeast homolog of RAB1) (Lynch-Day et al, 2010).…”
Section: Tethering and Fusion Of Incoming Phagophore Membranesmentioning
confidence: 99%
“…The association of Rab1 with the cytoplasmic surface of IC and cis-Golgi membranes, and its absence from the ER, has been demonstrated by EM Saraste et al, 1995;Satoh et al, 2003;Marie et al, 2012; Figure 2). The two Rab1 isoforms, Rab1A and RAB1B (93% homology), are recruited to IC membranes at ERES, show similar localizations by LM (Mochizuki et al, 2013; Figure 3(a)), but seem to play distinct roles in tubular and vesicular (long and short range) trafficking within the IC. Accordingly, live cell imaging and cell fractionation have shown that Rab1A mainly associates with IC tubules (Sannerud et al, 2006;Marie et al, 2009), while Rab1B interacts with GBF1 and evidently modulates COPI recruitment to globular IC domains Monetta et al, 2007;see below).…”
Section: Rab1 and Rab2mentioning
confidence: 99%
“…Visualization of IC dynamics using GFP-Rab1A showed that the pleiomorphic transport carriers arriving along MTs from the cell periphery do not move directly to cis-Golgi, but are targeted to the MTOC/centrosome that is normally positioned next to the Golgi ribbon. In cells displaying centrosome motility, for example, cells that are migrating or entering mitosis, the centrosome-targeted membranes can be resolved as a separate compartment, called the pericentrosomal IC (pcIC), which is distinct from the cis-Golgi-adjacent IC domain (Marie et al, , 2012Mochizuki et al, 2013; Figure 3(a)). Live imaging further showed that the separated pcIC and the Golgi communicate via tubular and globular carriers.…”
Section: Interconnected Membrane Systemmentioning
confidence: 99%